INTERLACED BILATTICES - Davidova, D. S. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2023)
In the present paper we have proved, that interlaced bilattices, one of the operations of which has identity element, is isomorphic to superproduct of two lattices.